Source apportionment of PM2.5 at urban and suburban areas of the Pearl River Delta region, south China - With emphasis on ship emissions - Tao, Jun; Zhang, Leiming; Cao, Junji; Zhong, Liuju; Chen, Dongsheng; Yang, Yihong; Chen, Duohong; Chen, Laiguo; Zhang, Zhisheng; Wu, Yunfei; Xia, Yunjie; Ye, Siqi; et al. (The Science of the total environment, 2017)
Daily PM2.5 samples were collected at an urban site in Guangzhou in 2014 and at a suburban site in Zhuhai in 2014–2015. Samples were subject to chemical analysis for various chemical components including organic carbon (OC), element carbon (EC), major water-soluble inorganic ions, and trace elements. The annual average PM2.5 mass concentration was 48±22μgm−3and 45±25μgm−3 in Guangzhou and Zhuhai, respectively, with the highest seasonal average concentration in winter and the lowest in summer at both sites. Regional transport of pollutants accompanied with different air mass origins arriving at the two sites and pollution sources in between the two cities caused larger seasonal variations in Zhuhai (>a factor of 3.5) than in Guangzhou (<a factor of 2.0). Positive matrix factorization (PMF) analysis identified six and five major source factors for PM2.5 in Guangzhou and Zhuhai, respectively. Ship emissions, a source factor previously ignored in making emission control policies in the Pearl River Delta region of south China, were among the top contributors to PM2.5 at both sites, accounting for >17% of PM2.5 mass concentrations. [Display omitted] •Elevated ship emission tracer elements (Ni and V) were found in PRD.•Contributions of ship emissions to PM2.5 were significant and were quantified.•Interregional and intraregional transport of pollutants are both important sources.